2015
DOI: 10.1007/s00125-015-3744-z
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cδ regulates nuclear export of FOXO1 through phosphorylation of the chaperone 14-3-3ζ

Abstract: Aims/hypothesis Forkhead box protein O1 (FOXO1) is a transcription factor essential for beta cell fate. Protein kinase B-dependent phosphorylation of FOXO1 at S256 (P-FOXO1) enables its binding to 14-3-3 dimers and nuclear export. Dephosphorylated FOXO1 enters nuclei and activates pro-apoptotic genes. Since our previous observations suggest that protein kinase C delta (PKCδ) induces nuclear accumulation of FOXO1, the underlying mechanism was examined. Methods In human islets, genetically modified mice and INS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Expression of 14-3-3ε is linked with insufficient insulin secretion and reduced β-cell mass [40]. The 14-3-3γ dimers and exportin-1 (chromosomal region maintenance-1)-dependent nuclear export binds to phosphorylated factor forkhead box protein O1 (FOXO1) by protein kinase B [41, 42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of 14-3-3ε is linked with insufficient insulin secretion and reduced β-cell mass [40]. The 14-3-3γ dimers and exportin-1 (chromosomal region maintenance-1)-dependent nuclear export binds to phosphorylated factor forkhead box protein O1 (FOXO1) by protein kinase B [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, reduced 14-3-3ζ levels induce mitochondrial-linked β-cell death [45]. Gerst et al suggested that nuclear 14-3-3ζ binds to P-FOXO1, thereby promoting nuclear extrusion of the transcription factor [40]. This additional role underlines the importance of 14-3-3ζ for β-cell function [45].…”
Section: Discussionmentioning
confidence: 99%
“…). In line with these influences on their targets, 14‐3‐3 proteins have often been referred to as chaperones . We suggest that this definition is not completely correct.…”
Section: ‐3‐3 Structure and Functionmentioning
confidence: 97%
“…INS-1E cells (a kind gift of P. Maechler and C. B. Wollheim, University of Geneva, Switzerland) are derived from a rat insulinoma and were cultured as described previously [22]. Briefly, the cells were cultured in RPMI1640 containing 11 mM glucose and supplemented with 10 % FCS, 10 mM Hepes, 2 mM L-glutamine, 1 mM Na pyruvate and 10 μM β-mercaptoethanol (Sigma, München, Germany) but without addition of antibiotics.…”
Section: Ins-1e Cells and Mouse Islets Culturementioning
confidence: 99%